Marketing Air Cargo and Courier Services in Oman as a Niche Logistics Market Segment and Delving into the Complex Intricacies of this High-Value Industry - Taderera, Faustino; Al Balushi, Mahmood Sakhi; Masengu, Reason (European Journal of Science, Innovation and Technology, 2023)
This research reflects on marketing air cargo and courier services in Oman as a niche logistics market segment and delves into the complex intricacies of this high-value industry. The study used the conceptual research method, where rich, diverse, and relevant literature reviews were collected and analysed to reach sensible factual conclusions on gaps in knowledge on marketing air cargo operations in Oman. The air cargo function was well-developed and made a huge contribution to the fiscus and the Oman economy. This area of air cargo research was a virgin territory in Oman, and much research is necessary. The findings revealed that further improvements in Oman to march GCC competitors, such as the UAE, Qatar, and Saudi Arabia, in air cargo operations were required. It was also established that it was not easy to attract Omanis to these air cargo marketing and operations jobs, especially female candidates, because of odd working hours as well as the need to travel regularly and be away from home for some periods at times. It was found that critical skills were in short supply, especially local top-grade skills, customs and investment rules and regulations, and infrastructure in Oman needed to be improved, as well as processing and turnaround time, to match best practices in the GCC and globally. Delayed deliveries and incorrect documentation were sometimes experienced due to customs, transport, and loading delays. The Covid 19 pandemic has brought several interesting lessons to the study of cargo movements. The sea freight was hit by a critical shortage of containers, and the sea cargo cost was rocked (Din et al., 2021). Oman has undoubtedly made great strides and is marching on for stardom and big achievements. The findings revealed that air cargo operations and marketing were hands-on and required many years of experience, and one excelled after going through the mill rather than straight from college. Some type of air cargo logistics apprenticeship was necessary for one to establish in the upper and middle echelons of the industry. This study highlights the importance of developing cargo centres with proper handling equipment and staff that can enhance their utilisation. The industry is too delicate and sensitive, and subject to many rules and regulations relating to health and safety, security, environmental protection, and anti-smuggling measures. Other researchers can conduct further research using longitudinal studies and possibly involving every key airport in the country. Two of the researchers are expatriate academics from Zimbabwe and would want their own home country, Zimbabwe, to learn the same lessons that Oman is learning so that Zimbabwe can further develop its own air cargo and courier industry. One researcher was an Oman citizen, an industrialist, and a part-time academic. This team of three researchers worked hard to put up this unique paper in an area that largely remained untouched and unexplored in both Oman and Zimbabwe. The Covid 19 pandemic has brought several interesting lessons to the study of cargo movements. The sea freight was hit by a critical shortage of containers, and the sea cargo cost was rocked (Din et al., 2021).